1987
DOI: 10.2307/1938801
|View full text |Cite
|
Sign up to set email alerts
|

Old‐Field Succession on a Minnesota Sand Plain

Abstract: Vegetation and soils were sampled in 22 old fields ranging in age from 1 to 56 yr since abandonment. Soil nitrogen concentration increased significantly with field age. Vegetation cover, total aboveground plant biomass, and litter cover increased significantly with soil nitrogen. Light penetration to the soil surface was negatively correlated with total plant biomass. Field age and soil nitrogen concentration were used as independent variables in simple regression and partial correlation analyses to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
250
3
6

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(275 citation statements)
references
References 32 publications
15
250
3
6
Order By: Relevance
“…Cedar Creek Natural History Area is located 45 km north of Minneapolis, Minnesota, USA (45°24'N, 93°12'W), and has a typical mid-continental climate with hot, humid summers and cold winters. The soil within this Weld consists of fine sand (Grigal et al 1974), and nitrogen is the primary mineral nutrient limiting plant productivity within this Weld (Tilman 1984(Tilman , 1987.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cedar Creek Natural History Area is located 45 km north of Minneapolis, Minnesota, USA (45°24'N, 93°12'W), and has a typical mid-continental climate with hot, humid summers and cold winters. The soil within this Weld consists of fine sand (Grigal et al 1974), and nitrogen is the primary mineral nutrient limiting plant productivity within this Weld (Tilman 1984(Tilman , 1987.…”
Section: Methodsmentioning
confidence: 99%
“…Light limitation is minimal because of a low standing plant biomass and limited litter accumulation. Fertilization and shading studies within the same Weld have shown that nitrogen is the main factor that determines the outcome of plant competition and nitrogen limits net primary productivity (Tilman 1984(Tilman , 1987(Tilman , 1990. Abandoned Welds in mid-central Minnesota show an early successional dominance by weedy annual plants, which are replaced by cool season C 3 grasses that have a dispersal advantage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En el segundo año estas malezas desaparecieron junto con el trigo no así el sorgo, como ocurre también en el oeste de Buenos Aires (D Angela et al, 1986). Esta comunidad puede considerarse la primera etapa de esta sucesión que es muy similar a la de otros ecosistemas de distintos lugares (Perino & Risser, 1972;Kaputska & Molenski, 1976;Collins & Adams, 1983;D Angela et al, 1986;Inouye et al, 1987;Lewis et al, 1987).…”
Section: Resultados Y Discusionunclassified
“…Las primeras especies en colonizar el área después de ser abandonada son las especies del cultivo previo (Bazzaz, 1968), en praderas norteamericanas; después de la etapa de malezas sigue una etapa de pastos anuales; luego otra de pastos cespitosos, y finalmente la pradera madura, formada fundamentalmente por los pastos indígenas, después de 40 años o más (Perino & Risser, 1972;Kaputska & Molenski, 1976;Collins & Adams, 1983;Inouye et al, 1987).…”
unclassified